In Silico Evaluation of Putative S100B Interacting Proteins in Healthy and IBD Gut Microbiota - Orsini, Massimiliano; Di Liddo, Rosa; Valeriani, Federica; Mancin, Marzia; D’Incà, Renata; Castagnetti, Andrea; Aceti, Antonio; Parnigotto, Pier Paolo; Romano Spica, Vincenzo; Michetti, Fabrizio (Cells (Basel, Switzerland), 2020)
The crosstalk between human gut microbiota and intestinal wall is essential for the organ’s homeostasis and immune tolerance. The gut microbiota plays a role in healthy and pathological conditions mediated by inflammatory processes or by the gut-brain axes, both involving a possible role for S100B protein as a diffusible cytokine present not only in intestinal mucosa but also in faeces. In order to identify target proteins for a putative interaction between S100B and the microbiota proteome, we developed a bioinformatics workflow by integrating the interaction features of known domains with the proteomics data derived from metataxonomic studies of the gut microbiota from healthy and inflammatory bowel disease (IBD) subjects. On the basis of the microbiota composition, proteins putatively interacting with S100B domains were in fact found, both in healthy subjects and IBD patients, in a reduced number in the latter samples, also exhibiting differences in interacting domains occurrence between the two groups. In addition, differences between ulcerative colitis and Crohn disease samples were observed. These results offer the conceptual framework for where to investigate the role of S100B as a candidate signalling molecule in the microbiota/gut communication machinery, on the basis of interactions differently conditioned by healthy or pathological microbiota.